Coins of the Cities of Arpi and Dyrrachion from Research on the Solin-Zaobilaznica Site (Archaeologia Adriatica, 2025)
The text presents two examples of coins from the Hellenistic period discovered during rescue archaeological research on the Zaobilaznica in 1986 and 1987. Coins from the Hellenistic period are not a common find in the Solin area. So far, finds of coins of Heraclea, Dyrrachion, Apollonia, Sifnos, bronze coins of Issa and coins of Alexander of Macedon have been documented in the area of Solin.
Keywords: Solin; Zaobilaznica; coins; Arpi; Dyrrachion